CURRENT VULNERABILITIES OF CRITICAL INFRASTRUCTURE: RISK ASSESSMENT AND PROTECTION - Chechyk , Maryna (Collection of scientific papers «ΛΌГOΣ», 2025)
Critical infrastructure is one of the most important elements of modern society, ensuring the continuous functioning of important industries such as energy, transportation, telecommunications, water supply, and others. One of the main aspects of security is identifying and eliminating the risks of exploiting vulnerabilities that can be used by attackers to attack and compromise systems. First of all, it is worth starting with an analysis of current vulnerabilities inherent in critical infrastructure enterprises.